Gelatin-based biomaterials and gelatin as an additive for chronic wound repair - Cao, Hongwei; Wang, Jingren; Hao, Zhanying; Zhao, Danyang (Frontiers in Pharmacology, 2024)
Disturbing or disrupting the regular healing process of a skin wound may result in its progression to a chronic state. Chronic wounds often lead to increased infection because of their long healing time, malnutrition, and insufficient oxygen flow, subsequently affecting wound progression. Gelatin—the main structure of natural collagen—is widely used in biomedical fields because of its low cost, wide availability, biocompatibility, and degradability. However, gelatin may exhibit diverse tailored physical properties and poor antibacterial activity. Research on gelatin-based biomaterials has identified the challenges of improving gelatin’s poor antibacterial properties and low mechanical properties. In chronic wounds, gelatin-based biomaterials can promote wound hemostasis, enhance peri-wound antibacterial and anti-inflammatory properties, and promote vascular and epithelial cell regeneration. In this article, we first introduce the natural process of wound healing. Second, we present the role of gelatin-based biomaterials and gelatin as an additive in wound healing. Finally, we present the future implications of gelatin-based biomaterials.